Respostas

A melhor resposta!
2013-12-17T19:50:14-02:00
A) 4 (x + 5) + 3 (x + 5) = 21
4x + 20 + 3x + 15 = 21
4x + 3x = 21 - 20 - 15
7x = - 14
x = - 14 ÷ 7
x = - 2

b) 8 (x - 1) = 8 - 4 (2x - 3)
8x - 8 = 8 - 8x + 12
8x + 8x = 8 + 12 + 8
16x = 28
x = 28 ÷ 16
x = 1,75

c) 2 (x + 5) - 3 (5 - x) = 10
2x + 10 - 15 + 3x = 10
2x + 3x = 10 - 10 + 15
5x = 15
x = 15 ÷ 5
x = 3

d) 4x - 1 = 3 (x - 1)
4x - 1 = 3x - 3
4x - 3x = - 3 + 1
x = - 2

e) 3 (x - 2) = 2x - 4
3x - 6 = 2x - 4
3x - 2x = - 4 + 6
x = 2

1 5 1
2013-12-17T19:56:21-02:00